Comparison of Genetic Variability Induced by γ Radiation and Tissue Culture in Sorghum - Jayaramachandran, M.; Kumaravadivel, N.; Kandasamy, G.; Eapen, Susan (International Journal of Bio-resource and Stress Management, 2011)
Two sorghum varieties viz., CO(S) 28 (grain sorghum) and CO(FS) 29 (fodder sorghum) were utilized for mutation and in vitro culture studies. The apical shoots with several unfurled pale yellow leaves and immature inflorescence at premeiotic stage were collected and cut into pieces of 1-5 cm long and used as explants and cultured for callus induction. Callus induction was noticed 4 weeks after inoculation. Subculturing was done every 2 weeks after callus induction. The embryogenic calli obtained were transferred to shoot regeneration medium and grown at 26°C under 16 hr photoperiod and cool white fluorescent light. Then the plantlets were cultured on rooting medium and transferred to glass house after hardening. The first generation plants derived from in vitro culture were termed as SC1 and its selfed progeny as SC2. The SC2 generation was raised in the field with two replications by following RBD. The data on quantitative traits were recorded in mutation studies. Three different dosages viz., 25KR, 35KR, 45KR and 50 KR, 60 KR and 70 KR were given to the varieties CO(S)28 and CO(FS)29 respectively. The M1 generation was raised in the field and 30 M1 plants were randomly selected and forwarded to M2 generation. The observations on quantitative trails were recorded for 150 plants per treatment per replication. The data were subjected to statistical analysis. In both grain and fodder sorghum, the gcv observed among the mutant plants generated through γ irradiation for yield contributing traits was higher than the gcv recorded among the soma clones generated through in vitro culture. However, the present study indicated that both mutation and in vitro culture techniques will serve as efficient tools to generate more variability to enhace the scope for further selection and improvement in sorghum.